Evolutionary time scales from the AGB to the CSPNe phase - Miller Bertolami, Marcelo Miguel (2019)
The transition from the asymptotic giant branch (AGB) to the final white dwarf (WD)stage is arguably the least understood phase in the evolution of single low- and intermediate-mass stars (0.8 ∼ < MZAMS/M ∼ < 8...10). Here we briefly review the progress in the last 50 yearsof the modeling of stars during the post-AGB phase. We show that although the main features,like the extreme mass dependency of post-AGB timescales were already present in the earliestpost-AGB models, the quantitative values of the computed post-AGB timescales changed everytime new physics was included in the modeling of post-AGB stars and their progenitors. Then wediscuss the predictions and uncertainties of the latest available models regarding the evolutionarytimescales of post-AGB stars